Design of Microcontroller Based Power Supply Unit with Multiple Input and Output - David, Fakokunde Babatunde (ALSYSTECH Journal of Education Technology, 2024)
This innovative project showcases a versatile power supply module, capable of delivering both AC and DC outputs, regardless of the input power source. This user-friendly device offers multiple output options from a single unit, catering to diverse power requirements. At its core, a microcontroller (8051) expertly manages the switch and relay configuration, ensuring seamless operation. Through rigorous simulation (Matlab/Simulink) and practical testing (prototype device), our results demonstrate the module's effectiveness in providing a reliable, multi-output power supply solution, enhancing convenience and efficiency.